(untitled) (Proceedings of Southern Federal University. Philology, 2019)
The goal of the article is to explore some linguistic means used in the English and American military mass media discourse to describe the present situation around the North Korea. The research is carried out in the semiotic aspect with the help of contextual and distributive methods of analysis. The verbal signs that define the participants of the described events, their actions, relations, values and anti-values, tangible and intangible resources, quantitative characteristics of the latter, are used not only to supply the Western readers with the information about internal and external policy of the country but also to form a biased representation of what is happening for the world community. Key words: linguasemiotics, verbal sign, linguistic manipulation, elective interpretation, military mass media discourse. DOI 10.23683/1995-0640-2019-4-21-30